Seekers : Toklo's story - Jolley, Dan.; Hunter, Erin.; Kurkoski, Bettina M (Los Angeles : TokyoPop ; New York : Harper, 2010)
Toklo, a young bear cub, dreams of being an important bear someday, and of always being close to his beloved brother Tobi, but when an older bear threatens them, they have to leave their territory and set off into the unknown.
Keywords: Bears -- Fiction; Brothers -- Fiction; Fantasy graphic novels; Graphic novels